(untitled) (Bangladesh Journal of Botany, 2010)
Aluminium at 10 ppm increased chl a in Aghrani, Gourab, Kanchan and Sourab; chl b and carotinoids in Fang-60, Kanchan and Sourab, though at 100 ppm inhibited chl a in all nine varieties, chl b in Akbar and Protiva and carotinoids in Aghrahani, Gourab, Kanchan, Protiva, and Sonalica. Proline content increased in the seedlings of all varieties and the root had relatively higher proline content than that of shoot. Stimulatory effect of Al3+ on proline content was higher in Kanchan. Proline content also increased in Akbar, Gourab and Sonalika. Al3+ stress induced increase in protein and reducing sugar contents was more in root than in the shoot. Hamatoxylin test of the root tips also revealed differential responses of the varieties to Al3+ stress. Key words: Aluminium stress; HYV wheat; Metabolites; Hematoxylin test; Efficiency ratio DOI: 10.3329/bjb.v39i1.5519 Bangladesh J. Bot. 39(1): 9-14, 2010 (June)